2019
DOI: 10.1016/j.healthplace.2019.03.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of the natural environment in disaster recovery: “We live here because we love the bush”

Abstract: This mixed-methods study explored the role of connection to the natural environment in recovery from the 'Black Saturday' bushfires that blazed across Victoria, Australia, in February 2009. Qualitative findings demonstrated that many participants had a strong connection to the natural environment, experienced considerable grief as a result of its devastation in the fires and drew solace from seeing it regenerate over the following months and years. Quantitative analyses indicated that a strong attachment to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 53 publications
0
25
0
Order By: Relevance
“…Figure 1 is a flowchart summarizing our search process and outcomes. This review found 60 articles that met the inclusion criteria [ 13 , 14 , 16 , 17 , 19 , 20 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 is a flowchart summarizing our search process and outcomes. This review found 60 articles that met the inclusion criteria [ 13 , 14 , 16 , 17 , 19 , 20 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , …”
Section: Resultsmentioning
confidence: 99%
“…Female gender was a statistically significant predictor of receiving mental health services. Block et al [38] 2019 Australia…”
Section: Cross-sectional Studymentioning
confidence: 99%
“…Consistent with cognitive models of depression, increased depressive symptoms during the bushfire period might be explained by feelings of inadequate personal control ( Beck, 2002 ), or an inability to influence final outcomes, as most Australians could not mitigate the threats of the bushfires through action. Indeed, grief and sadness have been previously reported by Australians in responses to the environmental damage caused by bushfires ( Block et al, 2019 ). While depressive symptoms did not increase significantly into the COVID-19 period, they remained elevated, which in combination with the increase in anxiety symptoms indicate a level of sustained psychological distress in the community.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, emerging evidence suggests that mutual reinforcement of public health messages and actions among community members has positive implications for health-related behaviors and compliance with public health directives during pandemics [ 30 ]. Restoring connections to the natural environment will have additional mental health benefits [ 31 ]. Working within existing community social structures and across a broad cross section of the community—with Elders, youth, local faith leaders and community groups—helps to establish respectful and collaborative relationships.…”
Section: Resultsmentioning
confidence: 99%